2018
DOI: 10.2298/abs170731041k
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute hyperhomocysteinemia induced by DL-homocysteine or DL-homocysteine thiolactone on serum biochemical parameters, plasma antioxidant enzyme and cardiac acetylcholinesterase activities in the rat

Abstract: The effects of acute hyperhomocysteinemia induced by DL-homocysteine or DL-homocysteine thiolactone on serum biochemical parameters, plasma antioxidant enzyme and cardiac acetylcholinesterase activities in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…On the other hand, the same study indicates an increase in MDA in hippocampus after 3 h 40 , which may be the result of increased concentrations of iron, lipid content and low activity of antioxidants in basal conditions 41 . Other autors demonstrated that acutely given Met increased SOD and GPx activity 1h after application, but decreased CAT activity in the rat brain cortex 42 . In another experiment SOD activity in the rat brain remained unchanged, which is consistent with the results obtained in the heart in our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the same study indicates an increase in MDA in hippocampus after 3 h 40 , which may be the result of increased concentrations of iron, lipid content and low activity of antioxidants in basal conditions 41 . Other autors demonstrated that acutely given Met increased SOD and GPx activity 1h after application, but decreased CAT activity in the rat brain cortex 42 . In another experiment SOD activity in the rat brain remained unchanged, which is consistent with the results obtained in the heart in our study.…”
Section: Discussionmentioning
confidence: 99%